Primary pharyngolaryngectomy with jejunal free flap reconstruction: a single centre's evolving experience. Issue 10 (1st May 2020) - Henrys, Courtenay; Slaughter, Thomas; Bernard, Anne; Perry, Christopher; Porceddu, Sandro; Panizza, Benedict
Abstract: Background: Head and neck squamous cell carcinoma, and in particular hypopharyngeal squamous cell carcinoma, has long been associated with disfiguring treatment options, significant morbidity and limited long‐term survival outcomes. Total pharyngolaryngectomy (TPL) with free flap reconstruction followed by post‐operative radiation therapy or chemoradiotherapy is a widely accepted treatment of choice for advanced disease of the hypopharynx. Methods: Our unit undertook a 11‐year review of all primary TPL patients aiming to provide an update on survival outcomes, morbidity, post‐operative complications and evolving management strategies. We report one of the largest single‐centre series to date with 89 patients undergoing primary TPL between 2003 and 2013, and compare these outcomes to 180 patients undergoing TPL at the same facility in the previous 23 years. Results: Between study periods, we saw a shift in patient population towards higher stage disease (T‐stage 3 or 4 97% 2003–2013; 68% 1979–2002) and increased nodal involvement (node positive 88% 2003–2013; 70% 1979–2002) without a subsequent reduction in 5‐year disease‐specific survival (52% 2003–2013; 52% 1979–2002) or 5‐year overall survival (32% 2003–2013; 33% 1979–2002). Abstract : Our unit undertook a 11‐year review of all hypopharyngeal squamous cell carcinomas treated with primary total pharyngolaryngectomy aiming to provide an update on survival outcomes, morbidity, post‐operative complications and evolving management strategies. We report one of the largest single‐centre series to date.